PENGARUH PRESTISE, PERSAINGAN DAN BAURAN PEMASARAN 7P TERHADAP KEPUASAN PELANGGAN FOUNTAIN ICE CREAM CAFÉ PLAZA MEDAN FAIR - melda lumbantobing; beby karina fawzeea (Jurnal Media Informasi Manajemen, 2013)
This research was to emphasize the effect of Prestige, Competition, 7P Mix Marketing towards consumer satisfaction Fountain Ice Cream Café Medan Fair Plaza. The objective of this research is to know the effect of Prestige, Competition and 7P Mix Marketing towards Consumer satisfaction Fountain Ice Cream Café Medan Fair Plaza.The kind of this research is assosiative research. The data that used consist of primer and secondary data. This research used 96 respondents which determined by using accidental sampling.The result of this research by multiple regression test shows that Prestige, Product, Price, and Phicycal Evidence have positive and significant effect towards Consumer Satisfaction Fountain Ice Cream Café Medan Fair Plaza, but the partial test showed that Prestige, Product, Price, and Phicycal Evidence have positive dan significant effect towards Consumer Satisfaction. Competition, Place, and Process have positive and insignificant effect towards Consumer Satisfaction effect towards Consumer Satisfaction while Promotion and People have negative and insignificant effect towards Consumer Satisfaction Fountain Ice Cream Café Medan Fair Plaza.Keywords: Prestise, Competition, Product, Price, Place, Promotion, People, Phicycal Evidence, Process, and Consumer Satisfaction.